Integrated simulation and optimization scheme of real-time large-scale water supply network: applied to Catalunya case study. (January 2015) - Sun, Cong Cong; Puig, Vicenç; Cembrano, Gabriela
This paper presents an integrated simulation and optimization modeling approach in order to provide the optimal configuration for large-scale water supply systems (LSWSS) in real time. Model predictive control (MPC) has been chosen to handle the complex set of objectives involved in the management of LSWSS. The computation of control strategies by MPC uses a simplified model of the network dynamics. The use of the combined approach of optimization and simulation contributes to making sure that the effect of more complex dynamics, better represented by the simulation model, may be taken into account. Coordination between simulator and optimizer works in a feedback scheme, from which both real-time interaction and extensive validation of the proposed solution have been realized using a case study based on the Catalunya regional water network.